2017
DOI: 10.1016/j.optcom.2016.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Simple pre-distortion schemes for improving the power efficiency of SOA-based IR-UWB over fiber systems

Abstract: International audienceIn this paper, we investigate the usage of SOA for reach extension of an impulse radio over fiber system. Operating in the saturated regime translates into strong nonlinearities and spectral distortions, which drops the power efficiency of the propagated pulses. After studying the SOA response versus operating conditions, we have enhanced the system performance by applying simple analog pre-distortion schemes for various derivatives of the Gaussian pulse and their combination. A novel pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Hence, the average signal power has to be reduced so as to meet the regular limit, leading to a significant impact on the power efficiency (degradation > 35%) at both operating points, specially for the noisy case. In our recent work [19], we have studied the power efficiency versus SOA input power while considering several peak-topeak voltages. It has been shown that high input powers bring strong nonlinearities specially at large V pp , and low powers are associated with a small signal-to-noise (SNR) ratio particularly at low V pp .…”
Section: Ir-uwb Over Fiber System Architecture and Soa Impact On mentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the average signal power has to be reduced so as to meet the regular limit, leading to a significant impact on the power efficiency (degradation > 35%) at both operating points, specially for the noisy case. In our recent work [19], we have studied the power efficiency versus SOA input power while considering several peak-topeak voltages. It has been shown that high input powers bring strong nonlinearities specially at large V pp , and low powers are associated with a small signal-to-noise (SNR) ratio particularly at low V pp .…”
Section: Ir-uwb Over Fiber System Architecture and Soa Impact On mentioning
confidence: 99%
“…Table II states the parameters of applied waveforms, besides to the power efficiencies and spectral characteristics evaluated at SOA output. BL 34 is defined as the left -34 dB bandwidth (distance between the lower frequency f L and f peak ), this criterion is useful to evaluate the spectrum in correspondence with GPS band [19]. As shown, the same waveforms are generated in electrical domain, and chirping has no drawback on the pulse spectral behavior.…”
Section: Bias Current Influencementioning
confidence: 99%
See 2 more Smart Citations
“…A particular scenario of UWB is the Impulse Radio, which is a cost effective approach offering a low order of generation complexity [5] together with a simple design at the receiver side if a non-coherent detection is adopted [6]. With the view to get a reach extension in the optical access network, a low cost Semiconductor Optical Amplifier (SOA) has been recently employed [7,8]. However, a performance degradation may occur due to the nonlinear effects and Amplified Spontaneous Emission (ASE) noise inherent to SOA.…”
Section: Introductionmentioning
confidence: 99%